Endodontic retreatment decision‐making: The influence of the framing effect - Thomas Kvist; Daniela Henelius; Agnesa Smakiqi (Wiley, 2023)
Abstract Objective The aim of this study was to explore the influence of a framing effect in retreatment decision‐making of a root‐filled tooth with asymptomatic apical periodontitis (AP). Method Two variants of a questionnaire were created in which the factual information about a root filled with AP was identical. The options in the first variant were framed in favor to wait and see (FW) and those in the other variant were framed in favor of retreatment (FR) Two hundred and forty‐eight volunteers were by chance given one of the two versions and were asked to choose between having retreatment or to wait and see. Results Of the 125 participants given the FW version, 69 (55.2%) chose to wait and see while out of the 123 participants who were given the FR version, 38 (30.9%) made the alike choice (p = .0002). Conclusion A framing effect is likely to play an essential role in endodontic retreatment decision‐making of root‐filled teeth with asymptomatic apical periodontitis.